Citizens’ images of a sustainable energy transition - Annukka Vainio; Vilja Varho; Petri Tapio; Anna Pulkka; Riikka Paloniemi (Elsevier, 2022)
Achieving a sustainable energy transition is crucial for mitigating climate change. Citizens' acceptance of the transition is important for it to succeed. We explored citizens' images of the future energy forms and energy system in Finland, and the drivers of a sustainable energy transition. The data gathered with an online questionnaire targeting an adult population 17–75 years of age (N = 1012) were analysed with exploratory factor analysis and multiple linear regression. Four dimensions of future energy forms were identified: next-generation renewables, fossil energy, bioenergy, and established renewable vs. nuclear energy. Four dimensions of the future energy system were also identified: renewing the energy market, domestic power, small-scale producers, and consumer awareness. Five transition drivers were likewise identified: mainstreaming renewable energy, international actors, individual actions, changing values and economy, and emancipatory change. Mainstreaming renewable energy emerged as the key driver of transition, followed by individual actions. Generally, the sustainable energy transition was strongly supported by citizens' images, but different socio-economic groups preferred somewhat different images. Thus, the diversity of consumers' and citizens’ roles in the transition needs to be acknowledged and encouraged in legitimate national energy policies.